Adaptive memristor-based LIF neuron circuit for energy efficient SNN crossbar array - M. S. Deepthi; H. R. Shashidhara; S. B. Rudraswamy (Cognitive Neurodynamics, 2026)

Impact of shade trees on soil aggregate stability and carbon sequestration in coffee agroforestry systems of the Western Ghats, India - Nandita Sinha; Mavinakoppa S. Nagaraja; Sonali Paul Mazumdar; S. Raghavendra; Ganapathi Guddekoppa; B. V. Champa; Deepthi Dechamma; Nurnabi Meherul Alam; Sudarshan Varma (Agroforestry Systems, 2026)

Chaos Theory-Based Downscaling for Future Rainfall Projections from Climate Models - B. Deepthi; Bellie Sivakumar (Water Resources Management, 2026)

Assessing machine learning and Physics-Informed models for Multi-Lead time sea surface temperature prediction in the Arabian sea - Akshay Sunil; B. Deepthi; Muhammed Rashid; Rahul Sreedhar; Gaurav Ganjir; S. Adarsh (Stochastic Environmental Research and Risk Assessment, 2025)

Biological Decontamination of Mycotoxigenic Fusarium verticillioides Using Lactiplantibacillus plantarum MYSN128 Isolated from Traditional Vellappam: Implications for Food Safety and Global Mycotoxin Management - G. Adithi; Rakesh Somashekaraiah; B. Shruthi; S. Divyashree; N. Deepa; P. R. Vanitha; R. Vasundaradevi; B. V. Deepthi; M. Y. Sreenivasa (Current Microbiology, 2025)

Computational modelling of thermal and mass transport in MHD nanofluid flow across a non-linear surface with chemical response and viscous dissipation - G. Jithender Reddy; V. V. L. Deepthi; R. Srinivasa Raju; B. Mallikarjuna Reddy; Farhan Ali (Modeling Earth Systems and Environment, 2025)

α-Glucosidase inhibitors from an endophytic fungus Edenia gomezpompae from Costus speciosus - B. M. S. Nilmini; Kavindya Samarakoon; Deepthi Yakandawala; Savitri Kumar; Nimal Adikaram; Lalith Jayasinghe; Hiroshi Araya; Yoshinori Fujimoto (Vegetos, 2025)

Saccharomyces cerevisiae MYSY1 as a promising probiotic isolate with antifungal properties against foodborne Aspergillus species - B. Shruthi; B.V. Deepthi; G. Adithi; P.R. Vanitha; M.Y. Sreenivasa (Biocatalysis and Agricultural Biotechnology, 2025)

Zebrafish as a model to assess the neurotoxic potential of propylene glycol ethers - Ramya Deepthi Puligilla; Noëmi Johanna Roos; Jan Stephan Bolten; Nancy B. Hopf; Marie-Gabrielle Zurich; Nikolai Barulin; Jörg Huwyler (Environmental Toxicology and Pharmacology, 2025)

Enhanced rainfall forecasting for Mumbai using data-driven ConvLSTM2D models at fine spatial and temporal scales - Akshay Sunil; Ajay Devda; R. Murthy; B. Deepthi (Natural Hazards, 2025)

Dual Metal Ion Sensing by an Azo Compound Derived from Thiazolo[3,2-a] Indole: A Selective and Sensitive Approach - Haitham K.R. Al-Sharifi; C. B. Meenakshy; K. S. Sandhya; Ani Deepthi (Journal of Fluorescence, 2025)

Spatial downscaling of rainfall from general circulation models: A chaos theory-based framework - B. Deepthi; Bellie Sivakumar (Atmospheric Research, 2024)

Shortest path length for evaluating general circulation models for rainfall simulation - B. Deepthi; Bellie Sivakumar (Climate Dynamics, 2023)

Towards assessing the importance of individual stations in hydrometric networks: application of complex networks - B. Deepthi; Bellie Sivakumar (Stochastic Environmental Research and Risk Assessment, 2023)

Performance assessment of general circulation models: application of compromise programming method and global performance indicator technique - B. Deepthi; Bellie Sivakumar (Stochastic Environmental Research and Risk Assessment, 2022)

Modeling future irrigation water demands in the context of climate change: a case study of Jayakwadi command area, India - Akshay Sunil; B. Deepthi; A. B. Mirajkar; S. Adarsh (Modeling Earth Systems and Environment, 2021)

Characterization of extremely halophilic archaeal isolates from Indian salt pans and their screening for production of hydrolytic enzymes - Deepthi Das; Isha Kalra; Kabilan Mani; Bhakti B. Salgaonkar; Judith M. Braganca (Environmental Sustainability, 2019)

Multifractal characterization of meteorological drought in India using detrended fluctuation analysis - S. Adarsh; D. Nagesh Kumar; B. Deepthi; G. Gayathri; S. S. Aswathy; S. Bhagyasree (International Journal of Climatology, 2019)
This study presents multifractal detrended fluctuation analysis (MF‐DFA) to describe the multifractality of Standardized Precipitation Index (SPI) series from 30 meteorological subdivisions of India estimated at different aggregation timescales (3, 6 and 12 months) based on long‐term monthly rainfall data sets of 1871–2016 period. The plots of fluctuation function and generalized Hurst exponents confirmed that multifractality is evident in most of the SPI series; however, it is found that its strength and persistency differ with timescale and space. The Hurst exponents of long‐term (SPI‐12) and medium‐term (SPI‐6) drought series of all subdivisions showed long‐term persistence irrespective of the climatic conditions of the region, while the short‐term droughts (SPI‐3) of six subdivisions displayed short‐term persistence. Further, the analysis by partitioning the data to four time spells: 1871–1905, 1906–1940, 1941–1975 and 1976–2016 showed that the persistency of long‐ and medium‐term drought is rather permanent. The analysis on changes in multifractal properties with respect to the climatic shift of 1976/1977 period showed that there is a clear increase in multifractal properties of all types of drought series in the recent past (post‐1976 period). This study also finds that the Hurst exponents and degree of multifractality of all types of droughts increase with increase in aggregation timescales. The multifractality of all the long‐term drought series (SPI‐12) and most of the SPI‐6 series are found to be due to correlation properties, while that of SPI‐3 is because of joint effect of correlation properties and the broadness of probability distribution.

Antiaflatoxigenic Potential of Cell-Free Supernatant from Lactobacillus plantarum MYS44 Against Aspergillus parasiticus - K. Poornachandra Rao; B. V. Deepthi; S. Rakesh; T. Ganesh; Premila Achar; M. Y. Sreenivasa (Probiotics and Antimicrobial Proteins, 2019)

Predicting personality from network-based resting-state functional connectivity - Alessandra D. Nostro; Veronika I. Müller; Deepthi P. Varikuti; Rachel N. Pläschke; Felix Hoffstaedter; Robert Langner; Kaustubh R. Patil; Simon B. Eickhoff (Brain Structure and Function, 2018)

Resting-state test–retest reliability of a priori defined canonical networks over different preprocessing steps - Deepthi P. Varikuti; Felix Hoffstaedter; Sarah Genon; Holger Schwender; Andrew T. Reid; Simon B. Eickhoff (Brain Structure and Function, 2017)

Heterosis and combining ability in rice as influenced by introgressions from wild species Oryza rufipogon including qyld2.1 sub-QTL into the restorer line KMR3 - Sudhakar Thalapati; Haritha Guttikonda; Naga Deepthi Nannapaneni; Prasad Babu Adari; C. Surendhar Reddy; B. P. Mallikarjuna Swamy; Anil K. Batchu; Ramana Kumari Basava; B. C. Viraktamath; Sarla Neelamraju (Euphytica, 2015)

Curdlan-like exopolysaccharide production by Cellulomonas flavigena UNP3 during growth on hydrocarbon substrates - Sushma Deepthi Arli; U. B. Trivedi; K. C. Patel (World Journal of Microbiology and Biotechnology, 2011)

Geochemical and statistical approach for evaluation of heavy metal pollution in core sediments in southeast coast of India - B. R. R. Seshan; U. Natesan; K. Deepthi (International Journal of Environmental Science and Technology, 2010)